(untitled) (Research, Society and Development, 2021)
The acquisition of information about the characteristics of the landscape is essential for planning the use and conservation of natural resources. In view of the above, the present study aims to provide geometric, topographic and hydrographic information on the Três Galhos river microbasin. For the acquisition of information we use software (QGIS, Google Earth and TrackMaker Free), altimetric images (ALOS satellite) and equations, and for the discussion of the results we use data from the literature. The Três Galhos river microbasin has an area of ​​23.24 km2, a perimeter of 26.13 km, an elongated shape, low susceptibility to flooding (geometric point of view), altitudes from 247 to 444 m, predominance of smooth undulating relief (45,1%), drainage network of 91.33 km, dendritic pattern, 6th drainage order (high condition for housing fish), 12.62 springs km-2 (high), drainage density of 3.93 km km-2 (very high), sinuosity index of 39.94% (main sinuous channel), maintenance coefficient of 254.5 m2 m-1 and concentration time of 2.28 h (low). Therefore, the information obtained from the Três Galhos river microbasin can assist in the planning and management of natural resources in the region, through institutions (public and private) and rural property owners, enabling the maintenance or improvement of the quality of life of current generations and future.